Natural Ressources and Conflict in Colombia: Complex dynamics, narrow relationships (2007)
There is a close relationship in Colombia between the political, economic, military, social, and environmental dimensions of the internal conflict. Although the military and social dimensions have been the object of multiple academic studies and political concerns, the environmental dimension has been neglected in both academic analyses and political diagnoses. The object of this article is to identify and analyze the various scenarios in which natural resources (oil, minerals, biodiversity, and fresh water) are connected to the political, economic and military dynamics of the Colombian conflict.